An Anti-EGFR/anti- HER2 Bispecific Antibody with Enhanced Antitumor Activity Against Acquired Gefitinib-Resistant NSCLC Cells - Si, Yan; Pei, Xinxin; Wang, Xiangfang; Han, Qianqian; Xu, Changzhi; Zhang, Buchang (Protein and Peptide Letters, 2021)
Background: Acquired resistance to epidermal growth factor receptor–tyrosine kinase inhibitors (EGFR-TKIs) is a recurrent phenomenon during clinical therapy of non-small-cell lung cancer (NSCLC). Studies have shown that HER2 is a key factor contributing to drug resistance in a variety of cancers. Furthermore, we have observed that HER2 is overexpressed in PC-9 NSCLC cells with acquired gefitinib-resistance (PC-9/GR) as compared to that in PC-9 cells. Objective: We hypothesized that blocking both EGFR and HER2 may serve as a potential strategy for the treatment of NSCLC with acquired gefitinib-resistance. Methods: To target both EGFR and HER2 simultaneously, we developed a bispecific antibody HECrossMAb, which was derived from a humanized Cetuximab and Trastuzumab. The binding affinity of HECrossMAb for EGFR and HER2 was measured using an enzyme-linked immunosorbent assay. The MTT assay was used to determine the effect of HECrossMAb on the proliferation of PC-9 and PC-9/GR cells in vitro. Finally, the effect of HECrossMAb on PI3K/AKT signaling and associated transcription factors was measured using western blot analysis. Results: Our results showed that HECrossMAb exerts enhanced cytotoxicity in both PC-9 and PC-9/GR cells by inhibiting the activation of PI3K/AKT signaling and expression of relevant transcription factors such as AEG-1, c-Myc, and c-Fos. Conclusion: Our results suggest that HECrossMAb may function as a potential therapeutic agent for treating NSCLC overexpressing EGFR and HER2.
Keywords: HECrossMAb